Effect of artificial baits on the catch efficiency of monofilament gill nets - Dartay, M.; Duman, E. (Wiley-Blackwell, 2014)
Greater success in catching fish with gill nets is possible if more the fish are attracted to the nets. Bait has been successfully used to lure fish into the gill nets. With the aim of increasing the catch efficiency of monofilament gill nets, a study was conducted between January 2009 and December 2010 to test the effect of artificial baits on the efficiency of 40, 50 and 55 mm monofilament gill nets in the Keban Dam Lake (Elazig/Turkey). The catch rate of the baited nets was compared to similar nets without bait. Baited nets caught 482 fish (71.8% of the total, seven species). Non-baited nets caught 189 fish (28% of the total, seven species). The majority of fish (238) were caught using baited gill nets with 40 mm mesh. The most commonly caught species was Capoeta trutta. The differences between the baited gill nets and non-baited gill nets were statistically significant (P < 0.05). Finally, it was understood that artificially baited monofilament gill nets had higher catch efficiencies than non-baited monofilament gill nets. Unlike most natural baits, artificial baits are re-usable and thus more economical in the long term.
Keywords: Rates